Salicylic acid modulates arsenic toxicity by reducing its root to shoot translocation in rice (Oryza sativa L.) - Singh, Amit P.; Dixit, Garima; Mishra, Seema; Dwivedi, Sanjay; Tiwari, Manish; Mallick, Shekhar; Pandey, Vivek; Trivedi, Prabodh K.; Chakrabarty, Debasis; Tripathi, Rudra D. (Frontiers in Plant Science, 2015)
Arsenic (As) is posing serious health concerns in South East Asia where rice, an efficient accumulator of As, is prominent crop. Salicylic acid (SA) is an important signaling molecule and plays a crucial role in resistance against biotic and abiotic stress in plants. In present study, ameliorative effect of SA against arsenate (AsV) toxicity has been investigated in rice (Oryza sativa L.). Arsenate stress hampered the plant growth in terms of root, shoots length, and biomass as well as it enhanced the level of H2O2 and MDA in dose dependent manner in shoot. Exogenous application of SA, reverted the growth, and oxidative stress caused by AsV and significantly decreased As translocation to the shoots. Level of As in shoot was positively correlated with the expression of OsLsi2, eﬄux transporter responsible for root to shoot translocation of As in the form of arsenite (AsIII). SA also overcame AsV induced oxidative stress and modulated the activities of antioxidant enzymes in a differential manner in shoots. As treatment hampered the translocation of Fe in the shoot which was compensated by the SA treatment. The level of Fe in root and shoot was positively correlated with the transcript level of transporters responsible for the accumulation of Fe, OsNRAMP5, and OsFRDL1, in the root and shoot, respectively. Co-application of SA was more effective than pre-treatment for reducing As accumulation as well as imposed toxicity.